Factors Affecting Softball Athletes' Performance: A Review of the Literature - Muhammad Fahrezi Harahap; Windi Indriani Br Ginting; Frendi Hotmartua Naingg; Oktaviani Pilbina Br Tarigan; Esmen Arberto Tarigan; Alvigho Jablin Bredo Ginting (Joska: Jurnal Isori Kampar, 2025)
Objectives: This systematic review aims to identify and synthesize the multifaceted factors influencing performance outcomes in softball athletes, encompassing physiological, psychological, technical, and contextual dimensions. Methods: A systematic literature search was conducted across five electronic databases (PubMed, Scopus, Web of Science, SPORTDiscus, and Google Scholar) from inception to October 2024. Studies examining performance determinants in competitive softball athletes were included. The PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines were followed for study selection, data extraction, and quality assessment. Results: Twenty-seven studies met the inclusion criteria, encompassing 2,847 softball athletes across various competitive levels. Key performance factors identified were categorized into five domains: (1) physical attributes (strength, power, speed, agility), (2) technical skills (batting mechanics, pitching velocity, fielding proficiency), (3) psychological factors (motivation, anxiety management, mental toughness), (4) anthropometric characteristics (body composition, height, limb length), and (5) contextual elements (coaching quality, training volume, competitive experience). Batting power demonstrated strong correlations with upper body strength and rotational power. Pitching performance was significantly associated with lower body strength, core stability, and kinematic efficiency. Psychological resilience emerged as a critical moderator of performance under competitive pressure. Conclusion: Softball performance is determined by a complex interplay of physical, technical, psychological, and contextual factors. Evidence suggests that integrated training approaches addressing multiple performance domains yield superior outcomes compared to isolated interventions. Future research should employ longitudinal designs and standardized assessment protocols to establish causal relationships and develop sport-specific performance models.